(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Tolerance as a philosophical problem is solved in the national culture, interpersonal and inter-faith relations. The solution of this problem depends on the specifics of the socializations of people, and it is socio-cultural and subcultural traditions. Studies of many foreign and domestic scientists show on a methodological basis. The current world crisis in economy, finance and human relations show the relevance of the study of the phenomenon of tolerance, scientific and theoretical basis of its nature and specificity. Globalization, a multipolar world, the liberal-democratic values have made the problem of tolerance prerequisite for regulating relations between peoples, nations, religions and ethnicities. These processes convert tolerance to political necessity. This, in turn, must be cultural norms. This is indicated by historical and actual experience at the international level and at the national-cultural. Key words: tolerance, value, globalization, mentality, ethnic relations, nation, ethnicity, interfaith harmony.